Djawa Baroe sebagai Media Propaganda Jepang di Jawa (1943-1945) - Imroatul Sholekah; Nurhadi Sasmita (Program Studi Ilmu Sejarah Fakultas Ilmu Budaya Universitas Jember, 2021)
This study discusses Djawa Baroe as a Japanese Propaganda Media in Java in 1943-1945. Djawa Baroewas a pictorial magazine published during the Japanese Occupation Government in Java as a medium for transferring information to the Dutch East Indies population containing propaganda news. The problems studied in this study are the press policy of the Japanese Occupation Government in Java, the form of Japanese Occupation Government propaganda in the fields of education, literature and art, socio-culture, and military as appearing in Djawa Baroe, as well as examining the impact of Japanese Occupation Government propaganda in the fields. The method used in this study was the historical method from Louis Gottschalk, which includes the stages of data collection, source criticism, interpretation and historiography. This study uses a political science approach and propaganda theory developed by Miriam Budiarjo and Laswell. When controlling the Dutch East Indies, the Japanese Occupation Government used the press as a means of propaganda, one of which was through Djawa Baroe. The pictures displayed in Djawa Baroe form a picture of every activity carried out by the Dutch East Indies in the fields of education, literature and art, socio-culture and military as an activity that seemed perfect for wartime. In fact, in real life, the activities displayed in Djawa Baroe are not the same, because the Javanese people experienced many hardships in life during the war.